Overexpression of Wnt5a in Bone Marrow-Derived Macrophages Promotes Osteoarthritis Progression - Li, Wenhui. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024-05.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Li Zeng.; Keyword: Pharmacology.